KINERJA KEUANGAN SEKTOR INDUSTRI PASAR MODAL INDONESIA DALAM ERA EKONOMI PASIFIK - Saerang, David Paul Elia; Ilat, Ventje (Universitas Sam Ratulangi, 2014)
By point of view of economics, Indonesia is one of most countries, who have strong fundamental factors because it was arose from global financial crisis in period of 1997 till 2008. By this fact, in world’s perception, Indonesia as a one country who have strong potential for era of 2020 and 2030, which is equal to others countries. The economic growth is also connecting with investment condition in capital market, and it is indicate that the role of investors are very important for economic growth acceleration in Indonesia. This study took 36 companies as sample in period of 2009 till 2012 and using multiple regression analysis for hypothesis testing. The results of analysis are show that, business cycle has not significant effect for share price, but partially, debt capacity, profitability, and market price ratio have significant effect for share price.